2019
DOI: 10.1155/2019/2726837
|View full text |Cite
|
Sign up to set email alerts
|

Providing Aging Adults Social Robots’ Companionship in Home-Based Elder Care

Abstract: Population aging is increasingly serious. The application of social robots for home-based elder care is an important way to solve this problem. Aging adults’ demands for social robots’ companionship affect robotic designs. This study aimed to investigate aging adults’ demands for social robots’ companionship and explored in which life situations it was appropriate to accompany aging adults by social robots. This study involved three phases. Phase 1 (an interview survey) collected the life situations in which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
3
Order By: Relevance
“…While using social robots with older adults may present certain ethical issues, such as loss of control, possible reduction in human contact, and declining privacy ( Pedersen et al, 2018 ; Van Maris et al, 2020 ), older adults have often indicated a desire to interact with them and received benefits from their use. For instance, research shows that OAs also desire companionship with robots in activities such as dining, resting, doing housework, and entertaining ( Chen et al, 2019 ). Social robots can also be designed to help OAs improve their levels of social participation by reminding and suggesting how they can connect with others in local or remote activities ( Cahill et al, 2018 ; Obayashi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…While using social robots with older adults may present certain ethical issues, such as loss of control, possible reduction in human contact, and declining privacy ( Pedersen et al, 2018 ; Van Maris et al, 2020 ), older adults have often indicated a desire to interact with them and received benefits from their use. For instance, research shows that OAs also desire companionship with robots in activities such as dining, resting, doing housework, and entertaining ( Chen et al, 2019 ). Social robots can also be designed to help OAs improve their levels of social participation by reminding and suggesting how they can connect with others in local or remote activities ( Cahill et al, 2018 ; Obayashi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite older adults encountering difficulties in many activities of daily life, a robot has been judged as an interesting solution only in some circumstances [ 20 , 71 ]. Older adults worry about being bothered by companion robots while resting; however, experts think that older adults might feel lonely and need companionship in these situations [ 80 ]. A similar study showed that older adults are more positive toward the listening robot than the speaking robot [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Auch andere Untersuchungen zeigten, dass soziale Roboter vor allem als Begleiter in sozialen Situationen wie einem gemeinsamen Essen, beim Fernsehen zuhause oder als Begleiter bei einem Spaziergang gewünscht sind (Chen et al. 2019 ; Karunarathne et al. 2019 ).…”
Section: Diskussionunclassified